2014
DOI: 10.1108/ijshe-09-2012-0079
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceptions of education for sustainable development

Abstract: Purpose – This study investigated whether a course which focused on raising students' awareness of sustainability, from a balanced perspective, that is, one which gives equal consideration to the social and economic aspects as well as the environmental would produce graduates with the knowledge and commitment required to drive the sustainability agenda forward. The paper aims to discuss these issues. Design/methodology/approach – An anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 15 publications
6
75
0
Order By: Relevance
“…Hicks [14] indicated that learning about global issues such as sustainability and acting upon it can never be solely a cognitive matter, but must also involve an affective understanding. Nonetheless, increasing knowledge may not automatically result in changes in awareness and actions [15], so educational institutions aim at development of deeper circular learning patterns, where the knowledge is reflected upon and questioned in learning loops before application [12,[16][17][18] Several studies have focused on students' perceptions of sustainability [19][20][21], the impact of the amount and type of coursework on students' conceptualizations of sustainability [22], and the relationships of demographic factors on students' environmental awareness, knowledge and behavior [23,24]. However, limited studies exist on the results of sustainability implementation in education, as was highlighted by Tilbury [25], and on students' learning progress about sustainability during their university studies, according to McKeown [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hicks [14] indicated that learning about global issues such as sustainability and acting upon it can never be solely a cognitive matter, but must also involve an affective understanding. Nonetheless, increasing knowledge may not automatically result in changes in awareness and actions [15], so educational institutions aim at development of deeper circular learning patterns, where the knowledge is reflected upon and questioned in learning loops before application [12,[16][17][18] Several studies have focused on students' perceptions of sustainability [19][20][21], the impact of the amount and type of coursework on students' conceptualizations of sustainability [22], and the relationships of demographic factors on students' environmental awareness, knowledge and behavior [23,24]. However, limited studies exist on the results of sustainability implementation in education, as was highlighted by Tilbury [25], and on students' learning progress about sustainability during their university studies, according to McKeown [26].…”
Section: Introductionmentioning
confidence: 99%
“…This is very vital because an educated public is required to carry out informed sustainability decisions that would affect the entire society. There is empirical evidence that even a single course, that encourages more active learning and involves an inquiry based approach, has been effective in positively changing students' perceptions of sustainability [21]. Also, courses must be not only instruments of delivering ESD, but instructors must be centrally involved in developing the concepts, content, pedagogy, evaluation, and research that will support the creation of ESD [7].…”
Section: Teaching and Research Related To Sustainabilitymentioning
confidence: 99%
“…Examples of such studies were conducted in several universities in USA [4,17,19], Europe-such as in Germany [15] and UK [13,20]-and in Australia [21]. In all these studies, students are quite aware about and are willing to support and participate in sustainable initiatives at their colleages/universities.…”
Section: Introductionmentioning
confidence: 99%
“…Related examples of such assessment/framework were carried out in the United States [19], Canada [20], and the United Kingdom [21]. Other studies were on HEIs' students' perception and assessment of campus sustainable development in the United States [4,22,23], Germany [24], the United Kingdom [25], Australia [26], and many more. A recent study carried out in Saudi Arabia investigated students' assessment of campus sustainability at the University of Dammam via the use of an SAQ [27].…”
Section: Introductionmentioning
confidence: 99%